Evaluating Resilience Co-benefits of Engineering With Nature® Projects - Kurth, Margaret H.; Ali, Rahim; Bridges, Todd S.; Suedel, Burton C.; Linkov, Igor (Frontiers in Ecology and Evolution, 2020)
An increasing abundance of projects demonstrate that coastal management strategies that align engineering and ecological objectives can deliver a wide range benefits. Better understanding how these strategies fare under stress is crucially important, including in comparison to traditional coastal engineering approaches, in order to inform where they might be a viable alternative or complement to conventional coastal storm risk management. In particular, the prospect that these strategies may be able to recover from disturbances and adapt to better survive future disturbances with minimal or no intervention is compelling. However, no formal accounting method exists to assess how ecosystem-based approaches contribute to the resilience of coastal systems, that is, their ability to prepare, absorb, recover, and adapt from stressors. An assessment rubric is developed and demonstrated for Engineering With Nature® projects and limitations and ways forward are discussed.